Cork powder waste: an overview - Gil, Luis (Biomass and Bioenergy, 1997)
k powder, the major waste from cork processing industries, is generated throughout the industrial cork process and originates from grinding, cutting and finishing operations. Since there are various types of cork and different industrial operations, different types of cork powders are obtained. These have a high heating value, which make it suitable for energy production as well as other characteristics suitable for other uses as described here
Keywords: Cork; industry wastes; waste characterization; waste utilization

Cork powder waste: an overview (Biomass and Bioenergy, 1997)
k powder, the major waste from cork processing industries, is generated throughout the industrial cork process and originates from grinding, cutting and finishing operations. Since there are various types of cork and different industrial operations, different types of cork powders are obtained. These have a high heating value, which make it suitable for energy production as well as other characteristics suitable for other uses as described here